Psychometric Evaluation of the Korean Version of the Adapted Illness Intrusiveness Rating Scale - Sun-Mi Chae, PhD, RN; Chun-Ja Kim, PhD, RN; Hyera Yoo, DNSc, RN (Elsevier, 2010)
To examine the psychometric properties of the Korean version of the adapted Illness Intrusive-ness Rating Scale (a-IIRS). The a-IIRS is a modified version of the original IIRS that measures illness-disruptions to daily life in patients with diverse diagnoses. While the psychometric properties of the original IIRS have been validated, no study has been conducted to validate the Korean version of a-IIRS. Methods: After translation and back-translation processes, the Korean version of a-IIRS was developed. A pilot test was conducted with 10 patients with chronic diseases. A convenience sample of 380 patients with diabetes, hypertension, and/or arthritis was used. Exploratory and confirmatory factor analyses, known-group technique, hypothesized relationships, internal consistency, and item analysis were tested. Results: Three factors were extracted from principal components analysis with varimax rotation: Relationships and Personal Development, Instrumental Life, and Intimacy. Confirmatory factor analysis corroborated the good fit of the three-factor model. Illness intrusiveness was significantly different among the study subjects categorized into three groups according to different health status: poor, fair and good. The instrument was positively correlated with the scales of fatigue and depression. The tool demonstrated high internal consistency with adequate item-total correlations. Conclusions: The findings are consistent with previous study results on IIRS and support the reliability and validity of the Korean version of a-IIRS. The instrument is culturally relevant for Korean patients with chronic diseases. Health care professionals need to consider illness intrusiveness when caring for patients with chronic diseases and promote their quality of life.